Penggunaan Finger Painting Untuk Meningkatkan Kreativitas Anak Usia 5-6 Tahun di TK Yaspi Tampubolon Tahun Ajaran 2023/2024 - Khairiyah, Ummi; Qalbi, Zahratul; Delrefi, Delrefi; Putera, Rafhi Febryan (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to determine the use of finger painting to increase the creative abilities of children aged 5 to 6 years. This research uses the Kemmis and McTaggart paradigm in conducting classroom action research (PTK). The research participants were 16 children from Group B of YASPI Tampubolon Kindergarten, consisting of equal numbers of boys and girls (8 boys and 8 girls). The data collection method used is direct observation using special tools in the form of observation sheets and interview sheets. Data analysis was carried out using quantitative descriptive methods, with success criteria set at an average creative percentage ?80% for children in Group B. Research findings showed a significant increase in children's creativity after their participation in finger painting activities as intervention. This activity gives young people the autonomy to produce works of art based on their own concepts and choose colors based on their preferences. The increase in creative power can be seen from the pre-action data which shows a percentage of 48.66%. The percentage of originality increased to 64.95% in Cycle I, and then increased to 87.05% in Cycle II. This research is considered effective because it has reached the predetermined threshold of percentage of creative power.